Leskovca I and II, Stone Age open-air sites on the Leskovca alp in the Krn Mountains - Turk, Matija; Podobnik, Tilen (Arheološki vestnik, 2024)
In the last two and a half decades, several open-air sites with stone artefacts attributed to the Mesolithic period have been found in the Julian Alps, in the mountains above the Upper Soča Valley. This article also presents mountain sites from this region, located some 150 metres apart on the Leskovca alp in the Krn Mountains and named Leskovca I and II. It discusses the finds collected on the surface and the results of the archaeological excavation at Leskovca II. Due to the absence of organic remains reliably associated with stone artefacts, the cultural-chronological definition of the two sites only relies on the typological and technological analysis of the stone artefacts. The results show the sites belong to either the Late Upper Palaeolithic (Epigravettian) or the Early Mesolithic (Sauveterrian).